Influence of Printing Strategies on the Microstructure and Mechanical Properties of Additively Manufactured Alloy 625 Using Directed Energy Deposition (DED-LB-p) - Florian Scherm; Haneen Daoud; Uwe Glatzel (Metals)
Directed energy deposition (DED-LB-p) is used for the production of large components due to the high deposition rates. The large number of process parameters and printing strategies makes it difficult to optimize this process to achieve the optimal properties. Intensive post-processing is still the main obstacle to the widespread use of this process. In this work, the influence of different printing strategies and process parameters on the microstructural and tensile mechanical performance at room temperature is investigated. The porosity is measured in both printing directions. The grain orientation and size are analyzed by EBSD. A very low porosity of less than 0.4% is found in all the printed samples. The samples printed with the optimized offset printing strategy show a significant improvement in tensile strength of 1000 MPa without heat treatment compared to the other processing routes.